Inflammatory myofibroblastic tumor of the lung: a comprehensive narrative review of clinical and therapeutic insights - Vasileios Leivaditis; Marianthi Baltagianni; Elias Liolis; Nikolaos Baltayiannis; Gabriela Stanc; Efthymia Souka; Pella Batika; Konstantinos Grapatsas; Levan Tchabashvili; Konstantinos Tasios; Andreas Antzoulas; Dimitrios Litsas; et al. (Polish Journal of Thoracic and Cardiovascular Surgery)
Inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal neoplasm classified by the World Health Organization as an intermediate malignancy with less than a 5% chance of metastasis. IMTs consist of myofibroblastic and spindle fibroblastic cells accompanied by inflammatory infiltration, primarily affecting patients under 16 years old, though they can also occur in adults. The etiology and pathogenesis of IMTs remain unclear, with possible contributing factors including inflammation, trauma, autoimmune diseases, prior surgery, viral infections, and uncontrolled myofibroblast proliferation. The primary treatment is complete surgical resection, which is associated with long-term survival and a significantly reduced recurrence rate of 2%, compared to 60% for incomplete resections. Chemotherapy is generally not recommended but may be necessary for unresectable tumors. Advances in histopathological diagnosis provide deeper insights into IMT biology, aiding in the selection of appropriate treatments. This paper presents a comprehensive review of the literature on this rare clinical entity.